2014
DOI: 10.1152/jn.00372.2014
|View full text |Cite
|
Sign up to set email alerts
|

Modification of persistent responses in medial prefrontal cortex during learning in trace eyeblink conditioning

Abstract: Siegel JJ. Modification of persistent responses in medial prefrontal cortex during learning in trace eyeblink conditioning.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
10
0

Year Published

2015
2015
2018
2018

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 49 publications
3
10
0
Order By: Relevance
“…We show here that in the absence of CS-evoked startle and freezing responses, most mice required four to eight training sessions (with baseline CR rates of 0–5%) before beginning to express CRs, which gradually increased over an additional approximately five sessions. Once learning began, the progression of learning was similar across mice and independent of the number of sessions needed before learning was observed, similar to the learning curves often reported for rabbits ( Kalmbach et al, 2010b ; Siegel, 2014 ). Furthermore, using the current training procedures mice were able to fully extinguish CRs within two to three training sessions (0–5% CR rates) and reacquired CRs to previous levels of performance within five sessions.…”
Section: Discussionsupporting
confidence: 82%
“…We show here that in the absence of CS-evoked startle and freezing responses, most mice required four to eight training sessions (with baseline CR rates of 0–5%) before beginning to express CRs, which gradually increased over an additional approximately five sessions. Once learning began, the progression of learning was similar across mice and independent of the number of sessions needed before learning was observed, similar to the learning curves often reported for rabbits ( Kalmbach et al, 2010b ; Siegel, 2014 ). Furthermore, using the current training procedures mice were able to fully extinguish CRs within two to three training sessions (0–5% CR rates) and reacquired CRs to previous levels of performance within five sessions.…”
Section: Discussionsupporting
confidence: 82%
“…The mPFC has also been implicated in other behaviors that rely on the temporal organization of information, including learning stimulus sequences (Barker et al, 2007;Devito and Eichenbaum, 2011;Hannesson et al, 2004a;Mitchell and Laiacona, 1998) and remembering which locations in an environment have been previously visited (Chiba et al, 1997;Hannesson et al, 2004b). At the physiological level, mPFC neurons have been found to sustain firing rates over short temporal intervals (Hattori et al, 2014;Rainer et al, 1999;Siegel, 2014;Takehara-Nishiuchi and McNaughton, 2008). These patterns parallel well-established observations of neuron activity in the primate dorsolateral prefrontal cortex (dlPFC) during working memory tasks (Fuster and Alexander, 1971;Kojima and Goldman-Rakic, 1982;Quintana and Fuster, 1992).…”
Section: Introductionsupporting
confidence: 66%
“…The mPFC has been revealed to connect with the cerebellum via the pontine nuclei in rodents 15 , rabbits 16 17 , non-human primates 18 and the humans 19 . Moreover, multiple-unit recording studies have shown learning-related neuronal activity in the mPFC during TEBC 20 21 22 23 24 . Pharmacological or physical interventions that interfere with neuronal activity in the mPFC not only impair the expression of acquired trace CRs 3 4 25 26 , but also prevent the CR acquisition 12 13 14 .…”
mentioning
confidence: 99%